Pasar Nongkrong Modern - Richard Juan Austen; Agustinus Sutanto (Jurusan Arsitektur dan Perencanaan, 2020)
The Special Capital Region of Jakarta (DKI Jakarta) is the country's capital and largest city in Indonesia. Jakarta as a large capital city has an attraction as a place to look for income, it is very attractive for residents from various regions in Indonesia to come to Jakarta who are settled and claim to be citizens of Jakarta. The number of migrants in Jakarta is around 68,500 people and it is predicted that as many as 60% live in Jakarta. Jakarta is a city with a fairly rapid economic growth rate. At present, more than 70% of state money is circulating in Jakarta. Since the early 1980s, the DKI Jakarta Government has been intensively building modern shopping centers, or commonly known as malls and plazas. At present Jakarta is one of the cities in Asia that has many shopping centers. In addition to luxury shopping centers, Jakarta also has many traditional markets and wholesale trade centers. For smaller environments, shopping centers for daily necessities are also available at affordable prices, such as Indomaret and Alfamart. The city of Jakarta as the capital of Indonesia focuses its development as the center of Indonesian business so that it is now densely filled with houses and tall buildings. The condition of the city of Jakarta is dense with residents and buildings, certainly there are many problems that arise, and the main problems of the city of Jakarta such as traffic jams, social problems and flooding. Traffic congestion makes Jakarta residents become lazy to leave the house so that an individualistic lifestyle makes social interaction decrease, also causes stress. The lives of Jakarta residents who live in high-rise buildings such as apartments that are mushrooming in Jakarta, which are very individual and cannot interact with the surrounding environment and daily activities are only